Health Interview Survey, 1965 ([Verlag nicht ermittelbar], 2010)
The purpose of the Health Interview Survey is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. There are six types of records in the 1965 survey, each in a separate data file. The Person file (Part 1) includes information on sex, age, race, marital status, Hispanic origin, education, veteran status, family income, family size, major activities, health status, activity limits, employment status, and occupation. These variables are found in the Condition and Hospital Episode files as well. The Person file also supplies data on height, weight, bed days, doctor visits, hospital stays, years at residence, and region variables. The Condition file (Part 2) contains information for each reported health condition, with specifics on injury and accident reports. The Prescribed Medicine file (Part 3) contains general demographic information, cost of medications, when medications were obtained, and conditions for which medications were prescribed. The Non-prescribed Medicine file (Part 4) contains general demographic information, where medications were obtained and purchased, as well as short-stay hospital episodes. The Diabetes file (Part 5) includes information regarding symptoms of diabetes, genetic variables, and treatment regimen variables. The Hospital Episode file (Part 6) provides information on medical conditions, hospital episodes, type of service, type of hospital ownership, date of admission and discharge, number of nights in hospital, and operations performed.